OPTIMALISASI KEUANGAN SYARIAH MELALUI PEMANFAATAN FINTECH: MITIGASI RISIKO PENIPUAN PINJAMAN ONLINE - Nurul Aisah; Ilham Wijaya Kusuma (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2024)
Teenagers today have a hedonistic nature that allows them to do various things to fulfill their hedonistic desires, so that they can be exploited by irresponsible individuals, such as illegal online loans. The main problems faced by partners are low knowledge about Islamic finance and the use of fintech and partners who often receive illegal online loan offers that take advantage of people's awareness of Fintech. The solution offered to the problems felt through this program is through counseling and education as well as training on the safe use of Fintech. The method used in this service is Focus Group Discussion (FGD) which consists of several stages, namely preparation, implementation and evaluation. As a result of this activity, partners experience an increase in knowledge about healthy sharia finance and an increase in partners' ability to use Fintech safely so that partners can make wise financial decisions